2022
DOI: 10.1021/acsabm.1c01138
|View full text |Cite
|
Sign up to set email alerts
|

Type-I Collagen/Collagenase Modulates the 3D Structure and Behavior of Glioblastoma Spheroid Models

Abstract: Multicellular tumor spheroids have emerged as well-structured, three-dimensional culture models that resemble and mimic the complexity of the dense and hypoxic cancer microenvironment. However, in brain tumor studies, a variety of glioblastoma multiforme (GBM) cell lines only self-assemble into loose cellular aggregates, lacking the properties of actual glioma tumors in humans. In this study, we used type-I collagen as an extracellular matrix component to promote the compaction of GBM aggregates forming tight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Actually, different subtypes of collagen have been investigated over the years and are related to GBM invasiveness. Recent findings have shown that GBM cell lines form tight spheroids in the presence of type I collagen and that the enzymatic cleavage of collagen affects spheroid morphology and increases cell migration [ 23 ]. In particular, the collagen alpha-2(I) chain (COL1A2) was found to be upregulated in GBMs compared with normal brain tissue, and it is related to poor progression-free survival and overall survival [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Actually, different subtypes of collagen have been investigated over the years and are related to GBM invasiveness. Recent findings have shown that GBM cell lines form tight spheroids in the presence of type I collagen and that the enzymatic cleavage of collagen affects spheroid morphology and increases cell migration [ 23 ]. In particular, the collagen alpha-2(I) chain (COL1A2) was found to be upregulated in GBMs compared with normal brain tissue, and it is related to poor progression-free survival and overall survival [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The applications of the 3D in vitro models described in Table 2 , Table 4 and Table 5 can be divided into three main fields: oncology, neurodegenerative diseases, and neurotoxicity. Most of the studies described in this review employ 3D neural models for inspecting their responses against drugs, treatments, and chemotherapeutic agents (e.g., temozolomide, epigallocatechin gallate, natural killer cells, nanoparticles, and rotenone) [ 33 , 34 , 35 , 41 , 42 , 70 , 91 , 92 ]. For these studies, the 3D models represent an advanced tool more closely resembling the characteristics of in vivo tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrogels used in tumour spheroid formation can be derived from the natural ECMs of the tumour stroma ( e.g. , Matrigel, 118 collagen, 119 and hyaluronic acid 120 ), natural materials ( e.g. , agarose 58 and alginate 59 ), or synthetic polymers ( e.g.…”
Section: Applications Of Droplet Microfluidics In Spheroidsmentioning
confidence: 99%
“…116,117 From the macroscopic view, tumour spheroids can be created by embedding individual cells into 3D hydrogel scaffolds. The hydrogels used in tumour spheroid formation can be derived from the natural ECMs of the tumour stroma (e.g., Matrigel, 118 collagen, 119 and hyaluronic acid 120 ), natural materials (e.g., agarose 58 and alginate 59 ), or synthetic polymers (e.g., PEG). 60 In the microfluidic device, the formation of tumour spheroids normally starts with the allocation of cells into individual hydrogel microparticles/ microcapsules, followed by the growth of cells into spheroids.…”
Section: Tumour Spheroidsmentioning
confidence: 99%